2020
DOI: 10.1088/1361-6528/ababc8
|View full text |Cite
|
Sign up to set email alerts
|

In situ TEM modification of individual silicon nanowires and their charge transport mechanisms

Abstract: Correlating the structure and composition of nanowires grown by the vapour-liquid-solid (VLS) mechanism with their electrical properties is essential for designing nanowire devices. In situ transmission electron microscopy (TEM) that can image while simultaneously measuring the current-voltage (I-V) characteristics of individual isolated nanowires is a unique tool for linking changes in structure with electronic transport. Here we grow and electrically connect silicon nanowires inside a TEM to perform in situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
(104 reference statements)
0
4
0
Order By: Relevance
“…In electron microcopy, in‐situ and operando methods are becoming increasingly more important. In particular, in transmission electron microscopy (TEM), the introduction of Micro Electronic Mechanical System (MEMS) chip‐based holders has led to the rapid development of methodologies allowing to directly relate structure and composition with material functionality (Alam et al, 2020; Allard et al, 2009; Creemer et al, 2010; Gaulandris et al, 2020; Mele et al, 2016; Niekiel et al, 2017; Vijayan & Aindow, 2019; Yokosawa et al, 2012; Zheng et al, 2022; Zintler et al, 2017). MEMS chips are also employed in conjunction with scanning electron microscopy (SEM) for in‐situ and operando experiments (Mølhave et al, 2004; Schwarzbach et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In electron microcopy, in‐situ and operando methods are becoming increasingly more important. In particular, in transmission electron microscopy (TEM), the introduction of Micro Electronic Mechanical System (MEMS) chip‐based holders has led to the rapid development of methodologies allowing to directly relate structure and composition with material functionality (Alam et al, 2020; Allard et al, 2009; Creemer et al, 2010; Gaulandris et al, 2020; Mele et al, 2016; Niekiel et al, 2017; Vijayan & Aindow, 2019; Yokosawa et al, 2012; Zheng et al, 2022; Zintler et al, 2017). MEMS chips are also employed in conjunction with scanning electron microscopy (SEM) for in‐situ and operando experiments (Mølhave et al, 2004; Schwarzbach et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…One important class of in‐situ /operando experiments involves electrical measurements, yielding the electrical or electrochemical response of materials/devices with nanoscale dimensions (Alam et al, 2020; Haas et al, 2019; Kamaladasa et al, 2015; Zheng et al, 2022). Such experiments have given insight into, for example, solid state battery dynamics (Basak et al, 2022; Hammad Fawey et al, 2016; Wang et al, 2020; Yang et al, 2016; Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The optimal model fitted according to the Poole-Frenkel law (Figure 4b) suggests that the surface of the GaN NW is composed of several traps. [45,46] which capture and store charges under continuous voltage biasing. Based on the aforementioned results from TEM observations, material analysis, and I-V sweeps, our results showed a different conduction mechanism.…”
Section: Conduction Mechanism Of the Memristive Gan Nw Devicementioning
confidence: 99%
“…Therefore, it can be used to obtain a better understanding of the fundamental physical phenomena associated with NW or nanotube materials [ 16 ]. In situ TEM can be used to observe the dynamic changes of NWs [ 16 , 17 , 18 ], control their growth [ 19 , 20 , 21 , 22 , 23 ], and induce the formation of nanotubes [ 24 , 25 ] and nanopores [ 26 ]. For example, Harmand et al observed the atomic layer nucleation by growing GaAs NWs in environmental TEM [ 27 ].…”
Section: Introductionmentioning
confidence: 99%